The Association Between Video Gaming and Psychological Functioning - von der Heiden, Juliane M.; Braun, Beate; Müller, Kai W.; Egloff, Boris (Frontiers in Psychology, 2019)
Video gaming is an extremely popular leisure-time activity with more than two billion users worldwide (newzoo, 2017). However, the media as well as professionals have underscored the potential dangers of excessive video gaming. With the present research, we aimed to shed light on the relation between video gaming and gamers’ psychological functioning. Questionnaires on personality and psychological health as well as video gaming habits were administered to 2,734 individuals (2,377 male, 357 female, Mage = 23.06, SDage = 5.91). Results revealed a medium-sized relation between intense video gaming and poor psychological functioning with regard to psychological symptoms, affectivity, coping, and self-esteem. Moreover, gamers’ reasons for playing and their preferred game genres were differentially related to psychological functioning with the most notable findings for distraction-motivated players as well as action game players. Future studies are needed to examine whether these psychological health risks reflect the causes or consequences of video gaming.